Mobility Design: Die Zukunft der Mobilität gestaltenBand 1: Praxis (De Gruyter, 2022)
Climate change and the scarcity of resources, but also the steadily increasing traffic make it indispensable to develop new solutions for environmentally friendly and people-friendly mobility. The smooth and safe transition from one form of mobility to another, the use of different individual, shared or public means of transport on one route, must be possible in the future in a comfortable and simple way in order to give people a positive mobility experience. Today, there are already concepts and realised infrastructure projects that make the future of sustainable and networked mobility tangible in an exemplary way. This volume focuses on the importance of design: over 60 pioneering projects from the fields of design, architecture and urban planning are presented with the help of photos, plan drawings and short texts. With this international overview, Mobility Design not only shows the current state of sustainable mobility systems, but is also dedicated to mobility as one of the most important design tasks of the future.